Other Revenue Raising Options (Tufts Archival Research Center, 2007)
Documents pertaining to increased cigarette taxes. Provides a list of other revenue raising options. Discusses background of the issue. Predicts such a tax raise would have a devastating economic impact on the tobacco industry, would lead to unemployment, would economically disadvantage states and the consumer price index. Accuses such a tax increase of providing an unstable revenue base. Argues that high cigarette taxes are regressive and unfair.